An isonormal process associated with a Brownian motion - Dorogovtsev, A.А.; Nishchenko, І.І. (Reports of the National Academy of Sciences of Ukraine, 2022)
In the article a new method for studying the properties of trajectories of a standard planar Brownian motion {B(t ); t ≥ 0} is proposed. The approach is as follows. The superposition of a stationary Gaussian field, that does not depend on B , with the process B itself is considered. The existence of local times and self-intersection local times of the obtained stationary process depends on the convergence of some multidimensional integrals along the trajectories of the Brownian motion B .